A Goal Programming Model for Controlling Fund Diversion and Payment Delays in MBG Program - I Nyoman Sutapa (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2026)
The Free Nutritious Meal Program (MBG) involves a tiered flow of funds from the National Nutrition Agency (BGN) to foundations that contract local catering partners. In practice, two recurrent problems emerge: partial diversion of program funds and delays in payments to caterers. These issues threaten service quality and the financial sustainability of small catering providers. This paper develops a mathematical model that combines principal–agent theory and goal programming to support policy design for BGN. The foundation’s utility captures legal margin, potential diversion, and expected monetary penalties that depend on audit intensity and audit effectiveness. The principal (BGN) pursues three goals simultaneously: minimizing total diverted funds, minimizing weighted payment delays, and limiting total audit cost. Individual rationality (IR) and incentive compatibility (IC) constraints are incorporated to ensure foundations are willing to participate and prefer honest behavior. The resulting nonlinear goal programming formulation provides a structured way to explore trade-offs and to select audit and penalty parameters consistent with MBG objectives. A small numerical illustration demonstrates how the model operates and how policy parameters influence outcomes.